2018
DOI: 10.1371/journal.pgen.1007626
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic SUMO remodeling drives a series of critical events during the meiotic divisions in Caenorhabditis elegans

Abstract: Chromosome congression and segregation in C. elegans oocytes depend on a complex of conserved proteins that forms a ring around the center of each bivalent during prometaphase; these complexes are then removed from chromosomes at anaphase onset and disassemble as anaphase proceeds. Here, we uncover mechanisms underlying the dynamic regulation of these ring complexes (RCs), revealing a strategy by which protein complexes can be progressively remodeled during cellular processes. We find that the assembly, mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 36 publications
1
47
1
1
Order By: Relevance
“…However, depletion of ULP-1 does not have a discernible effect on meiotic chromosome segregation ( Figure 5F). It should be noted that a recent report found ULP-1 in the midbivalent and also attributed a more important role for ULP-1 during meiosis I (Davis-Roca et al, 2018). These results show that ULP-1 is an essential protein but the lethality is unlikely to arise due to meiotic defects.…”
Section: Ulp-1 Is An Active Sumo Protease In Vivo and In Vitrosupporting
confidence: 61%
See 3 more Smart Citations
“…However, depletion of ULP-1 does not have a discernible effect on meiotic chromosome segregation ( Figure 5F). It should be noted that a recent report found ULP-1 in the midbivalent and also attributed a more important role for ULP-1 during meiosis I (Davis-Roca et al, 2018). These results show that ULP-1 is an essential protein but the lethality is unlikely to arise due to meiotic defects.…”
Section: Ulp-1 Is An Active Sumo Protease In Vivo and In Vitrosupporting
confidence: 61%
“…The SUMO protease ULP-1. A recent paper has found that ULP-1 depletion does have a more dramatic impact on chromosome segregation (Davis-Roca et al, 2018). A possible explanation for this discrepancy is the long RNAi incubations used in the mentioned study.…”
Section: Sumo-dependent Regulation Of Bub-1 and Cls-2 Localisationmentioning
confidence: 82%
See 2 more Smart Citations
“…Slides were washed a final time and mounted in 0.5% p-phenylenediamine in 90% glycerol, 20mM Tris, pH 8.8, sealed with nail polish, and stored at 4°C prior to imaging.The following antibodies were used: rat anti-AIR-2 (1:500,Davis-Roca et al 2017), rabbit anti-SEP-1 (1:200, gift from Andy Golden), rabbit anti-BIR-1 (1:800, this study), mouse anti-SUMO (1:500, gift from Federico Pelisch), rabbit anti-BUB-1 (1:1000, Davis-Roca et al26 2018), rabbit anti-ASPM-1 (1:5000, gift from Arshad Desai), Mouse anti-a-tubulin-FITC (1:500, DM1a, Sigma) and rabbit anti-KLP-19 (1:2500, this study). KLP-19 and BIR-1 polyclonal antibodies were generated by Covance using recombinant GST-BIR-1 (Full length protein) andGST-KLP-19 (amino acids 371-1084) as antigens (purification performed as inDavis-Roca et al 2018). Antibody sera was then affinity purified and used at indicated concentrations.…”
mentioning
confidence: 99%